Dechlorination of monochlorobenzene by using electrochemical method - Abdul Jalil, Aishah; Tokuda, Masao (2004)
A new dechlorination system was carried out by electrolysis of a N, N-dimethylformamide solution containing a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a metal anode. Monochlorobenzene as a substrate was dechlorinated to benzene in this system, and the product was analyzed by gas chromatograph. Effect of temperature, type of anode material and solvent was investigated and it was also found that the rate and current efficiency for the benzene production were greatly improved when naphthalene was used as a mediator. In the Presence of naphthalene, the reduction of chlorobenzene occurs indirectly compared to its direct reduction at the platinum cathode to give complete dechlorination.